2007
DOI: 10.1038/mt.sj.6300141
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by Hsp104 and Hsp27 in Lentiviral-based Rat Models of Huntington's Disease

Abstract: Huntington's disease (HD) is an inherited neurodegenerative disorder caused by an expansion of glutamine repeats in the huntingtin (htt) protein. Abnormal protein folding and the accumulation of mutated htt are hallmarks of HD neuropathology. Heat-shock proteins (hsps), which refold denatured proteins, might therefore mitigate HD. We show here that hsp104 and hsp27 rescue striatal dysfunction in primary neuronal cultures and HD rat models based on lentiviral-mediated overexpression of a mutated htt fragment. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 49 publications
1
101
0
Order By: Relevance
“…The accumulation of misfolded proteins that have amyloid characteristics (a tertiary structure that is rich in β-sheets and can be visualized by staining with dyes such as Congo red and Thioflavin S) is thought to result from improper folding of the mutant proteins as well as insufficient clearance mechanisms 129 . Endogenous chaperones, in particular the heat-shock proteins, prevent misfolding and aggregation of mHtt, Tau and Aβ 130 , and their overexpression is protective against neurotoxic insults such as excitotoxicity 131 (Suppl Table S4). …”
Section: Protein Aggregation and Clearance Mechanisms In Ad And Hdmentioning
confidence: 99%
“…The accumulation of misfolded proteins that have amyloid characteristics (a tertiary structure that is rich in β-sheets and can be visualized by staining with dyes such as Congo red and Thioflavin S) is thought to result from improper folding of the mutant proteins as well as insufficient clearance mechanisms 129 . Endogenous chaperones, in particular the heat-shock proteins, prevent misfolding and aggregation of mHtt, Tau and Aβ 130 , and their overexpression is protective against neurotoxic insults such as excitotoxicity 131 (Suppl Table S4). …”
Section: Protein Aggregation and Clearance Mechanisms In Ad And Hdmentioning
confidence: 99%
“…4,[36][37][38] Discussion ClpB/Hsp104 proteins have the ability to modulate aggregate formation and toxicity and to "catalyze" the disaggregation and recovery of protein aggregates in yeast, 12 Escherichia coli, 39 mammalian cell cultures, and animal models of HD and Parkinson's disease. [16][17][18][19][20] Several mechanistic models have been proposed to explain these experimental observations. These models include (i) Hsp104-mediated inhibition of protein misfolding and aggregation, (ii) diversion of proteins towards non-toxic pathways, and (iii) disruption and dissociation of prefibrillar and fibrillar toxic aggregates.…”
Section: Binding Of Aβ Can Be Monitored By Atp Turnover Of Hsp104 Andmentioning
confidence: 99%
“…Huntington's disease (HD)], mammalian cell cultures, and yeast models of HD. [16][17][18][19][20] Others have shown that Hsp104 alone can disassemble preformed Sup35 and Ure2 prion fibrils. 2,3 However, the molecular mechanisms underlying these effects remain poorly understood (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…small HSP HSP27 (HSPB1) AD/ Aβ Reduced Aβ aggregation in vitro and toxicity on cells [98] and in mice [99]; alters tau dynamics in mice [100]; reduced polyQ aggregation and toxicity in cells [101] and by viral delivery in rats [102] but not transgenic mice [103]; reduced α-synuclein fibril AD/Tau HD/Htt AD deficits in mice [120]; polyQ in mice [121]; mutant SOD1 in mice [122].…”
Section: Chaperone Family Chaperone Disease/protein(s) Commentsmentioning
confidence: 99%